(untitled) (Minerva, 2019)
According to E. García Novo’s works about the actor’s entrances and his announcement in the tragedies of the fifth century, the author of this article tries to find some announcements in the Sophoclean fragments. The method of the survey is based upon the formulaic language of this kind of passages.